Fitzgerald & Kingsley's electric machinery - Umans, Stephen D. (McGraw-Hill Education, 2014)
This seventh edition of Fitzgerald and Kingsley's Electric Machinery by Stephen Umans was developed recognizing the strength of this classic text since its first edition has been the emphasis on building an understanding of the fundamental physical principles underlying the performance of electric machines. Much has changed since the publication of the first edition, yet the basic physical principles remain the same, and this seventh edition is intended to retain the focus on these principles in the context of today's technology.